Ethnicité et « renaissantisme » ethnique chez les peuples autochtones de la République sakha (Yakoutie) - Berre-Semenov, Marine Le (Strates, 2007)
Marine Le Berre Semenov. Born-again etnicity of small people from Sakha republic (Yakoutia) M. le Berre Semenov analyses closely the “born-again ethnicist” identity strategy of the Sakha elites, who have tried by this means to anchor their cultural and political power in their territory during the last fifteen years, only to lose it recently through the political revision recommended by Vladimir Putin in his desire to control their republics’ considerable mining wealth. In her opinion, this “identity” strategy has caused new and difficult divisions. M. Leberre Semenov analyse la stratégie identitaire ethniciste des élites sahkas qui ont essayé par ce biais durant les quinze dernières années d’asseoir leur pouvoir politique et culturel sur leur territoire, pour s’en voir récemment dépossédées par la révision politique préconisée par Vladimir Poutine, désireux de contrôler les richesses minières considérables de leur république. Selon cet auteur, cette stratégie « identitaire » a créé de nouvelles divisions difficiles à surmonter.